Patty's toxicology - Bingham, Eula; Cohrssen, Barbara; Patty, F. A. 1897-1981 (John Wiley & Sons, 2012)
Provides a new and international perspective to interpreting industrial toxicology, and discusses new subjects such as nanotechnology, flavorings and the food industry, reactive chemical control to comprehensive chemical policy, metalworking fluids, and pharmaceuticals.